Peningkatan Perekonomian Umkm Desa Puhjajar Kecamatan Papar Kabupaten Kediri Melalui Penerapan Inovasi Mesin Perajang Lontongan Kerupuk Otomatis - Istiqlaliyah, Hesti; Nadliroh, Kuni; Fauzi, Ah. Sulhan; Nugroho, Wibowo Harso; Sugianto, Arif (Universitas Nusantara PGRI Kediri, 2023)
Puhjajar is one of the villages in Papar District, Kediri Regency with the majority of the population making their living as producers of realizeyah crackers. They are members of associations, each of which consists of 11 craftsmen, where each craftsman has four to six members. The realizeyah crackers produced by the people of Puhjajar village are very famous among the cracker industry, especially in Kediri. In fact, in the marketing of these realizeyah crackers, they are sent outside Java and overseas. However, the problem arises as the market for realizeyah cracker products increases, namely that the realizeyah cracker producers have not been able to increase their production capacity. So there are often delays in delivery which can result in disappointing consumers. This happens because the production process is quite long, and raw materials are sometimes difficult to obtain. It was from this problem that the Nusantara University PGRI Kediri community service team tried to help solve the problems faced by producers by designing an automatic cracker cracker chopping machine. The results obtained after using this machine were an increase in production capacity, which initially only reached 80kg/day to around 350kg/day. Manufacturers are of course greatly helped by the existence of this chopping machine, they are ultimately able to meet the quite high market demand.